Braided science field schools: cultivating professional fluency in Indigenous-centered archaeology - Tushingham, Shannon; Carney, Molly; Scher, Naomi (Frontiers in Environmental Archaeology, 2026)
This paper presents a replicable model for transforming archaeological field schools into Braided Science programs that center Indigenous self-determination, robust Tribal collaboration, and integrated Cultural Resource Management (CRM) training. Grounded in the Indigenous-led pedagogy of Two-Eyed Seeing, this curriculum intentionally weaves Western scientific methods with oral histories, land-based protocols, and reciprocal stewardship. At its core is epistemological fluency—the capacity to recognize, switch between, and integrate diverse ways of knowing. Building on this concept, we define heritage professional fluency as a framework that emerges from braided science and equips students to generate actionable knowledge through collaborative, decolonized research. While no single field school can impart every technical and community-engagement skill, we argue that building professional fluency provides an essential foundation upon which graduates can continue to develop. Traditional field schools that emphasize academic research leave graduates underprepared for careers dominated by the CRM sector and the imperative for collaborative, ethically informed practice, perpetuating colonial dynamics. Through the Washington State University (WSU) Field School in Indigenous Collaboration, First Foods, and Cultural Resource Management at Indian Creek—a collaborative field school held in 2023 on Kalispel Tribal lands—we demonstrate how we navigated three entrenched barriers: (1) conflicting institutional goals and data-ownership conventions; (2) financial and accessibility constraints that limit participation; and (3) disciplinary fragmentation separating academic, CRM, and Indigenous archaeology. By aligning research with Kalispel priorities—traditional foodways and landscape stewardship—our Tribal-academic-CRM partnership shows that meaningful collaboration is achievable but requires significant individual commitment and structural reform. We call for comprehensive change—addressing dwindling tenure-track positions, rising tuition and field-school fees, and persisting access inequities—to align archaeological training with the evolving realities of academia and public archaeology. This case study offers a practical framework built with braided knowledges for reimagining field schools as dynamic laboratories of ethical practice, rigorous skill-building, and community-driven research.